Memória atávica: a estética da loucura em Mário Quintana - Barata Júnior, Carlos Roberto Rodrigues (2016)
This work aims to investigate the meanings of the trope “madness” and its many derivatives in the work of the Brazilian poet Mario Quintana (1906-1994). The Southern poet worked for over half a century with an aesthetic unified plan, like a tapestry of recurring images, in an attempt to question the concepts of reason and conscience. The poem Atavismo (1977) offers itself as a central axle to our analysis. Guided by Atavismo, this study observed the terms “madness” and “poetry” have the same genesis: an atavistic memory. In order to do so, it was necessary to consider inferences about atavism, a concept from Biology concerned to a special type of memory and about memory itself. Because its redundant insistence with the adjective “atavist” as an attribute of memory, the poet lead us to the perception that the discussion about madness/poetry turns around a collective problem, that is a social problem in relation with time and the values of time. The comprehension is that the terms madness/poetry are built as an antithesis of specific social settings like political, artistic, economic and cultural backgrounds. Trying to achieve a comprehension of such antithesis that defends more spontaneous ways of life, his work walks towards its end analyzing the tropes and aesthetical resources with which the poet embodied his plan: the child, the madman, Trebizon and other attachés in the Quintanian linguistic cast. Since we have been working with a very articulated poetics, a connected reading of the poems is desirable, which does not mean hermetic or exclusive. However, this approach does not prevent lay hold of other texts and explanatory elements that support this research with theoretical, critical, aesthetic and philosophical contributions. Therefore, the intersection of the poems with the voices of texts like Sophocles (497?-406? BC), William Shakespeare (1560?-1616), Machado de Assis (1839-1908), Mikhail Bakhtin (1895- 1975), Henri Bergson (1859-1941), Maurice Halbwachs (1877-1945), Salvador Dalí (1904-1989), Jacques Le Goff (1924-), Michel Foucault (1926-1984), Ecléa Bosi among others. Such voices promote richer critical notes about a Brazilian work spread over a lifetime in defense of a humanity beyond Cartesian logic.